2009
DOI: 10.1002/lary.5541121301
|View full text |Cite
|
Sign up to set email alerts
|

Navigational Risks Associated With Sinus Surgery and the Clinical Effects of Implementing a Navigational System for Sinus Surgery

Abstract: The patient populations in groups A and B were determined to have similar demographic profiles. Significantly more sinuses, specifically in the frontal location, were entered in group B compared with group A. Adjusted for the number of sinuses treated, the median operative times did not differ significantly between groups. Major and minor complication rates were similar in both groups and were consistent with the published literature. In a community hospital setting, once an electromagnetic guidance system bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 140 publications
(169 reference statements)
0
41
0
Order By: Relevance
“…1206,1207 Numerous publications include complication rates. In a comparison of 400 patients whose ESS was performed with IGS and a historical cohort of patients in whom IGS was not employed, Reardon 1205 showed comparable complication rates, despite more extensive surgery in the IGS patients. Fried et al 1206 were able to associate a reduced complication rate with the use of IGS through a comparison of a patient cohort of ESS cases performed with ESS and historical controls; of note, the IGS patients had greater surgical complexity.…”
Section: Xd4 Surgical Principles/techniques: Image Guidancementioning
confidence: 96%
See 2 more Smart Citations
“…1206,1207 Numerous publications include complication rates. In a comparison of 400 patients whose ESS was performed with IGS and a historical cohort of patients in whom IGS was not employed, Reardon 1205 showed comparable complication rates, despite more extensive surgery in the IGS patients. Fried et al 1206 were able to associate a reduced complication rate with the use of IGS through a comparison of a patient cohort of ESS cases performed with ESS and historical controls; of note, the IGS patients had greater surgical complexity.…”
Section: Xd4 Surgical Principles/techniques: Image Guidancementioning
confidence: 96%
“…1204 It must be remembered that the use of IGS is often associated with more extensive surgery, presumably due to the benefits of using the technology. 1205,1206 Both in practice and in published reports, ESS cases performed with IGS tend to be more complex than those cases performed without IGS; thus, a bias exists when interpreting some of the literature on the use of IGS and its benefits.…”
Section: Xd4 Surgical Principles/techniques: Image Guidancementioning
confidence: 99%
See 1 more Smart Citation
“…This, of course, will vary, but once established, others have also found that it does not increase surgical time significantly. 6 Another limitation with the current stereotactic technology is that it only enables a surgeon to navigate with images obtained before the surgical intervention. Although soft tissue deformation is limited in lateral orbital wall decompression, the appeal of real-time imaging of the changing intraoperative anatomy during the course of the procedure is clear.…”
Section: Bck Patelmentioning
confidence: 99%
“…They are widely accepted as useful tools for intraoperatively identifying important anatomical structures and assisting in the exact positioning of surgical instruments, especially when conditions are complex because of the loss of surgical landmarks as a result of previous surgeries or tumor destruction [1][2][3].…”
Section: Introductionmentioning
confidence: 99%